Math for engaged learning : business mathematics - Lim, Yvette F.; Nocon, Rizaldi C.; Nocon, Ederlina G.; Ruivivar, Leonor A. (Quezon City : Sibs Publishing House, Inc., 2016)
"The Math for Engaged Learning (MAFEL) series conforms to the requirement of the K to 12 math curriculum which develops math skills and processes, critical thinking skills, and problem solving skills." it emphasizes the development of values and attitudes as well as the maximum use of mathematical tools in learning."
English text.
Keywords: Business mathematics; Mathematics